Effect of Peer Tutoring Strategy on Upper Basic II Students' Achievement and Retention in Basic Science and Technology in Otukpo LGA, Benue State. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study examined the Effect of Peer Tutoring Strategy on Upper Basic II Students' achievement in Basic Science and Technology in Otukpo LGA, Benue State. Two research questions were asked and answered and two hypotheses were tested at 0.05 level of significance. A pre-test post-test quasi-experimental research design was adopted for the study. Simple random sampling techniques were used to sample 85 (44 Male and 41 Female) students in two intact classes from the population of 4,834 upper basic II students. Basic Science and Technology Achievement Test (BSTAT) and Basic Science and Technology Retention Test (BSTRT), instruments were used for data collection. A reliability coefficient of 0.79 was obtained using, kuder-Richardson 20 formula. Data were analyzed using mean and standard deviation, to answer research questions while the null hypotheses were tested using analysis of Covariance (ANCOVA). Findings of the study showed that there is a statistically significant difference between the mean achievement scores of students taught Basic Science and Technology with peer tutoring instructional strategy and those taught with lecture method, among others. Based on the findings, it was concluded that appropriate use of peer tutoring instructional strategy in teaching Basic Science and Technology would enhance students’ achievement and retention in Basic Science and Technology, in Otukpo LGA. Therefore, it was recommended that Basic Science and Technology teachers should endeavor to incorporate peer tutoring strategy into the teaching of Basic Science and Technology so as to increase achievement and retention in the subject.